2018
DOI: 10.5455/jice.20171011075112
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical Documentation of Traditional Knowledge about Medicinal Plants used by Indigenous People in Talash Valley of Dir Lower, Northern Pakistan

Abstract: to obtain ethnobotanical data from the local herbalist and elder villagers. Quantitatively, the ethnobotanical data were analyzed by using indices, Use Value, Relative frequency of citation, and Informant Agreement Ratio. Results: The study identified a total of 50 medicinal plant species belonging to 33 botanical families and 46 genera in the 17 villages. Lamiaceae with 6 species is the dominant family, and herbs (68%) the main sources of herbal formulations. Leaves (41%) are the main parts for ethnomedicine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 37 publications
4
20
0
1
Order By: Relevance
“…Inhabitants of the study area use 63% of the herbal preparations as oral intake, whereas rest 37% were applied topically. These results were analogous to previous reports [36, 67, 68, 72, 94, 95]. Poultice, rubbing, and paste were common topical methods as reported in previous studies [51, 96].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Inhabitants of the study area use 63% of the herbal preparations as oral intake, whereas rest 37% were applied topically. These results were analogous to previous reports [36, 67, 68, 72, 94, 95]. Poultice, rubbing, and paste were common topical methods as reported in previous studies [51, 96].…”
Section: Resultssupporting
confidence: 92%
“…(◆) = plants with similar use(s); (∎) = plants with dissimilar use (s); (●) = plants not reported in a previous study; Condition/ailment written in bold indicate the most preferred use for a given plant; *Plant uses, which are not reported in a previous study. 1: Ahmad et al [20]; 2: Hussain et al [60] 3: Shaheen et al [61]; 4: Amjad et al [59]; 5: Ajaib et al [62]; 6: Safeer et al [63]; 7: Shabir et al [64]; 8: Ahmad and Habib, [65]; 9: Qaseem et al [66]; 10: Khan et al [67]; 11: Wali et al [68]; 12: Ijaz et al [69]; 13: Hussain et al [70]; 14: Aziz et al [71]; 15: Ahmad et al [39]; 16: Aziz et al [50]; 17: Gulzar et al [45]; 18: Umair et al [36]; 19: Zahoor et al [72]; 20: Kayani et al [38]; 21; Umair et al [73]; 22: Fatima et al [74]
Fig. 3Life form distribution pattern of the reported plant species in the study area
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Most commonly the herbal medicines were prepared through powder (25.3%), followed by decoction (16.5%), plant extract (8.8%), paste (7.7%), poultice (5.5%), chewing (4.4%), juice, ash, frying in oil, cooked, poherb, through rubbing, and herbal tea (3.3% each), eaten as raw, herbal bath, and oil (2.2% each), and pills, and through steam (1.1% each) (figure 6). Such a wide range of preparations of herbal medicines have also been reported in various parts of Pakistan (Khan et al 2018;Ahmad et al 2014;Mahmood et al 2103;) as well as in other parts of the world (Jima and Megersa 2018;Belayneh and Bussa 2014;Kadir et al 2014;Song et al 2013). Local people of Phulgran applied plants through different routes.…”
Section: Methods Of Preparation and Administrationmentioning
confidence: 86%
“…However, research shows that literacy levels of people determined the mode of treatment [30]; the less educated preferred traditional methods of treatment where as the well educated preferred modern methods of health care. Research over the years has shown low literacy levels among research respondents: [31,32,33,26].…”
Section: Education and Plant Knowledgementioning
confidence: 99%